Covid-19 Pandemic in Indonesia: A Critique for Humanitarian Intervention - Irin Oktafiani (Masyarakat Indonesia, 2022)
The Covid-19 pandemic challenged countries worldwide to overcome the complex crisis and resulting in every country’s had to create humanitarian interventions to protect its the citizens. This study paper aims to examine whether Indonesia’s government intervention at the beginning of the pandemic was unsuccessful and gained some issues over it. This study analyses Indonesia’s initial regulations during the pandemic in some news and how the interventions at the beginning of the pandemic were full of blunders in four ways. First is, to explain that the regulation made by Indonesia’s government was not prioritising the most vulnerable groups who was most vulnerable. Second, the blunders in the national media and lack of coordinations to spread the crisis awareness of the crisis. Third, lack of collaborations with with and among stakeholders and as well as complicated bureaucracy. The last is the political intention, which obscureds the intervention for the sake of humanity. It is, therefore, Indonesia’s humanitarian interventions during the commencement of the pandemic that was were not effective and should be reevaluated as a pandemic intervention lesson learnt in the future.